Low Concentrations of Caffeine and Its Analogs Extend the Lifespan of Caenorhabditis elegans by Modulating IGF-1-Like Pathway - Du, Xiaocui; Guan, Yun; Huang, Qin; Lv, Ming; He, Xiaofang; Yan, Liang; Hayashi, Shuhei; Fang, Chongye; Wang, Xuanjun; Sheng, Jun (Frontiers in Aging Neuroscience, 2018)
Caffeine has been reported to delay aging and protect aging-associated disorders in Caenorhabditis elegans. However, the effects of low concentration of caffeine and its analogues on lifespan are currently missing. Herein, we report that at much lower concentrations (as low as 10 µg/ml), caffeine extended the lifespan of C. elegans without affecting food intake and reproduction. The effect of caffeine was dependent on IGF-1-like pathway, although the insulin receptor homologue, daf-2 allele, e1371, was dispensable. Four caffeine analogues, 1-methylxanthine, 7-methylxanthine, 1,3-dimethylxanthine, and 1,7-dimethylxanthine, also extended lifespan, whereas 3-methylxanthine and 3,7-dimethylxanthine did not exhibit lifespan-extending activity.